2021
DOI: 10.1002/ecy.3429
|View full text |Cite
|
Sign up to set email alerts
|

Big bees spread disease: body size mediates transmission of a bumble bee pathogen

Abstract: Trait variation can have important consequences for the outcomes of species interactions. Even though some traits vary as much within species as across related species, models and empirical studies typically do not consider the role of intraspecific trait variation for processes such as disease transmission. For example, many pollinator species are in decline because of a variety of stressors including pathogens, but the role of intraspecific trait variation in mediating disease dynamics is rarely considered. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
5
2
Order By: Relevance
“…Specifically, larger bee species and pollen specialists had higher parasite prevalence and richness. Larger bees forage over longer distances [33] and produce more faeces [51], which has been linked with parasite transmission [51]. In contrast to our findings, previous studies have found that smaller bee species [52] and smaller individuals [51] host more parasites than larger bees.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Specifically, larger bee species and pollen specialists had higher parasite prevalence and richness. Larger bees forage over longer distances [33] and produce more faeces [51], which has been linked with parasite transmission [51]. In contrast to our findings, previous studies have found that smaller bee species [52] and smaller individuals [51] host more parasites than larger bees.…”
Section: Discussioncontrasting
confidence: 98%
“…Larger bees forage over longer distances [33] and produce more faeces [51], which has been linked with parasite transmission [51]. In contrast to our findings, previous studies have found that smaller bee species [52] and smaller individuals [51] host more parasites than larger bees. More research is needed to examine how host traits related to movement ecology affect parasitism.…”
Section: Discussioncontrasting
confidence: 98%
“…On each flower, we placed one 10 μl drop of inoculum using a micropipette. We used 10 μl because it is within the natural range for a single B. impatiens fecal event (7 ± 5 μl, mean ± SD) (Van Wyk et al, 2021), and we did not add sucrose because B. impatiens feces typically does not contain sugar (Figueroa et al, 2019). We did not consider other compounds that may be found in feces.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of warming temperatures on insect body size is of particular concern (Gardner et al, 2011) because this trait is tightly correlated with ecological function in nature. For example, larger dung beetles transfer more nutrients into soil (Stanbrook et al, 2021), larger‐bodied pollinators carry more pollen (Földesi et al, 2021) and transmit more parasites (Van Wyk et al, 2021), and larger mosquitoes can ingest a greater volume of blood (Rocha‐Santos et al, 2021). Additionally, larger insects often have higher fecundity (Honĕk, 1993), fly longer distances (Jahant‐Miller et al, 2022; Yang et al, 2016), and have higher mating success (Zhang et al, 2021) than their smaller conspecifics.…”
Section: Introductionmentioning
confidence: 99%